2022
DOI: 10.1007/s11082-022-04367-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the spreading properties of vortex beam in turbulent biological tissues

Abstract: Presenting the intensity development of a circular Laguerre-cosh-Gaussian (CLChG) beam in turbulent mouse biological tissues is the major goal of the current work. Using the power spectrum refractive index from Schmitt's model and the extended Huygens-Fresnel integral, the propagation formula of the CLChG beam is produced. In order to determine the spreading properties of the studied beam, analytical expressions of the CLChG beam's effective beam size in turbulent mouse biological tissues are constructed. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It is commonly recognized that variations in salinity and temperature affect the refractive index of oceanic turbulence. Research on the effects of oceanic water temperature and salinity fluctuations, as well as the degree of polarization, mutual coherence function, spreading spherical waves, scintillation index, beam wander and average aperture on laser beam propagation have all been extensively studied (Chen et al, 2013;Lu et al, 2014;Baykal, 2016;Yang et al, 2017;Chib et al, 2023;Alharbi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly recognized that variations in salinity and temperature affect the refractive index of oceanic turbulence. Research on the effects of oceanic water temperature and salinity fluctuations, as well as the degree of polarization, mutual coherence function, spreading spherical waves, scintillation index, beam wander and average aperture on laser beam propagation have all been extensively studied (Chen et al, 2013;Lu et al, 2014;Baykal, 2016;Yang et al, 2017;Chib et al, 2023;Alharbi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The provided results show that beams with smaller orbital angular momentum quantum numbers and larger initial half-pulse width are able to mitigate the turbulence effects. In addition, the propagation of Laguerre-Gaussian vortex and circular Laguerre-cosh-Gaussian beams in turbulent mouse biological tissues is studied in [7,8]. Accordingly, intensity evolution of partially coherent Flattened Hermite Cosh-Gaussian beam in turbid tissue like scattering medium is studied in [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was recently revealed that, by means of a spiral orthogonal zone plate, one may employ different sorts of optical vortices (Rafighdoost and Sabatyan 2016). In recent years, several papers have examined the creation of a laser beam with phase singularities (Khonina et al 1992;Saad et al 2016;Ebrahim et al 2017;Nossir et al 2021;Belafhal and Nebdi 2014;Belafhal and Saad 2017;Chib et al 2023a;Chib et al 2023b;El Halba et al 2022;El Halba et al 2017;Ebrahim et al 2022). In 2016, Sabatyan et al (Sabatyan et al 2016) are treated the generation of the square array of optical vortices by a multiregional spiral square zone plate (MRSSZP), which is subdivided into a few regions.…”
Section: Introductionmentioning
confidence: 99%